(3JeGQjf eMdhdI aj GdGbJUGO GdhMOhjs - (3eHGQc(B, (3HdGdWIs ((3GdGScfOQjI(B:s (3eDSSI GdKbGaI GdLGeYjI(B,s, 2009)
(3JeGQjf h Mdhd Mhd fXQjI GdWdH h fXQjI GdYQV h GdJhGRf , fXQjI GdeSJgdc h fXQjI GdefJL , fXQjI GdJcGdja h GdJhGRf aj GdCShGbs
Keywords: (3GdEbJUGO Gdcdjs; (3GdEbJUGO(B- (3fXQjGJs; (3GdGbJUGOs